A natural special-shaped MXene/bamboo evaporator with synergistic hydrothermal management for solar water purification - Jinhong He; Zongpei Zhang; Tianqing Shu; Weisheng Yang; Xiaoxu Ma; Jingren Ma; Meiling Chen; Fengshan Zhang; Guigan Fang; Huining Xiao; Jingquan Han (Desalination, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

Study on the removal effect of Enteromorpha polysaccharide on heavy metal-organic composite pollution - Xue Shen; Yingqiang Li; Meiling Li; Yaru Zai; Xue Han; Shida Zhang; Jin Wang; Zhigang Yang; Yang Song (Journal of Environmental Chemical Engineering, 2026)

Effects of different dark septate endophyte species on growth, Pb tolerance and associated physiological responses in Astragalus membranaceus under Pb stress - Gen Li; Meiling Wu; Qingqing Liu; Yashuo Tian; Simiao Wang; Yibang Zhang; Qing Dang; Fei Cao; Li Han (Plant and Soil, 2026)

Shifting patterns in tropical lake phytoplankton communities coinciding with anthropogenic nutrient and pollutant trends - Dongna Yan; Yongming Han; Patrick Rioual; Jianghu Lan; Sifan Zan; Yalan Tang; Huijia Zhang; Meiling Guo; Eric Capo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A mid-Cretaceous (late Albian–early Turonian) stable isotope record from southern Tibet – Pristine or diagenetically altered? - Meiling Han; Gang Li; Alexander Wheeler; Ulrich Heimhofer; Jörg Mutterlose (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

PPAR γ changing ALDH1A3 content to regulate lipid metabolism and inhibit lung cancer cell growth - Xinyuan Tian; Xiaoping Bai; Yunqi Han; Yu Ye; Meiling Peng; Hongwei Cui; Kai Li (Molecular Genetics and Genomics, 2025)

A novel “WRF+AutoML” framework for enhanced heat estimation in urban environments - Meiling Gao; Huifang Li; Fei Chen; Mengzi Zhou; Guijun Yang; Dun Zhu; Dawei Han; Zhenhong Li (Sustainable Cities and Society, 2025)

Study on the evolution and prediction of carbon emission from land use change in Tulufan-Hami basin under the influence of urbanization and climate change - Meiling Huang; Yusuyunjiang Mamitimin; Abudukeyimu Abulizi; Rebiya Yimaer; Bahejiayinaer Tiemuerbieke; Han Chen; Tongtong Tao; Yunfei Ma (Environment, Development and Sustainability, 2025)

Impacts of human activities on vegetation dynamics amid climate change: A case study of the Hanjiang River Basin (China) - Xiaofei Li; Peiyue Li; Meiling Gao; Dawei Mu; Dawei Han (Journal of Environmental Management, 2025)

Late Albian–early Turonian calcareous nannofossils from southern Tibet — Implications for preservation, biostratigraphy and palaeoecology - Meiling Han; Gang Li; Ulrich Heimhofer; Jörg Mutterlose (Cretaceous Research, 2025)

Characteristics and mechanisms of sea (salt) water intrusion in Laizhou City, Shandong Province, China - Linghao Kong; Hongxian Chu; Guohua Hou; Jiao Zeng; Liyuan Zhao; Xiangcai Han; Yachao Li; Faqiao Zhou; Meiling Yin; Xuzhen Zhang (Frontiers in Marine Science, 2025)
Sea (salt) water intrusion is a significant and ongoing geological disaster, and in recent years, it has become a notable concern for Laizhou City, Shandong Province. To identify the characteristics and mechanism of sea (salt) water intrusion in Laizhou City, samples of different types of water bodies (such as seawater, freshwater, slightly brackish water, brackish water, saline water, and brine) were systematically collected from the coastal zone area. The hydrochemical composition and evolution characteristics of the water bodies and the current situation, trends, and causes of sea (salt) water intrusion were analyzed. In 2020, the sea (salt) water intrusion reached 645.76 km 2 (including 151.64 km 2 of serious intrusion area), which is the largest ever recorded. The sea (salt) water intrusion had a strip-sheet distribution. From land to sea, groundwater gradually transitioned from the HCO 3 ·SO 4 ·Cl-Ca type to SO 4 ·Cl-Na·Ca and SO 4 ·Cl-Na types and then evolved to the Cl-Na type. Furthermore, from land to sea, the dominant cations and anions shifted from Ca 2+ and HCO 3 - to Na + and Cl - . The influence of seawater or brine gradually increased, that of Ca 2+ and HCO 3 - gradually decreased; whereas that of Cl - and Na + gradually increased, showing a division zone of freshwater → slightly brackish water → brackish water → saline water → seawater (brine) in the macroscopic territory. The freshwater, slightly brackish water, and brackish water bodies in the study area were controlled by evaporation and concentration processes and rock weathering leaching, whereas the saline water and brine were primarily controlled by evaporation and concentration processes. Groundwater salinity in the study area mainly originates from sea (salt) water intrusion, and locally groundwater salinity mainly originates from mineral dissolution or human activities. In addition, significant cation exchange adsorption occurred in slightly brackish and brackish water. Overall, these results will help to prevent and control seawater intrusions and improve disaster management.

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Characteristics, sources, and health risks of fine particulate matter in Wuhan subway, China - Ji-Liang Lü; Qing Han; Zhen Wang; Min Tao; Xun Hu; Meiling Cao; Qingzhu Huang; Mengdie Shi; Zhenyu He; Xiaohu Zhao (Science of The Total Environment, 2025)

Autophagy in skeletal muscle dysfunction of chronic obstructive pulmonary disease: implications, mechanisms, and perspectives - Xiaoyu Han; Peijun Li; Meiling Jiang; Yuanyuan Cao; Yingqi Wang; Linhong Jiang; Xiaodan Liu; Weibing Wu (Journal of Zhejiang University-SCIENCE B, 2025)

Current advances in human-induced pluripotent stem cell-based models and therapeutic approaches for congenital heart disease - Meiling Cao; Yanshan Liu; Ying Sun; Ruiyi Han; Hongkun Jiang (Molecular and Cellular Biochemistry, 2025)

A mini-review on polyvinyl alcohol/lignin (nano)composites: Preparation, applications and perspectives - Meiling Han; Yu Zhang; Ying Zhang; Qing Ye; Mika Sillanpää; Xinli Zhu; Weijun Yang (Sustainable Chemistry and Pharmacy, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

Integrated effect of aspect ratio and tree spacing on pedestrian thermal comfort of street canyon - Xiaoping Chen; Meng Han; Jinyu He; Hang Ma; Meiling Han; Yanhong Liu; Xiaogang Wu (International Journal of Biometeorology, 2024)

A novel multi-level reverse logistics network design optimization model for waste batteries considering facility technology types - Meiling He; Qipeng Li; Xiaohui Wu; Xun Han (Journal of Cleaner Production, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

Research on the impact of the national ecological demonstration zone on green total factor productivity: Evidence from China - Chunlai Yuan; Meiling Shang; Zhaojie Han; Jiating Wang (Journal of Environmental Management, 2024)

Identification of dynamic changes in volatile compounds and metabolites during the smoking process of Zhenba bacon by GC-IMS combined metabolomics - Shuai Han; Meiling Ke; Ling Wang; Haidong Ma; Guofei Wu; Lianxu Zhu; Tao Zhang; Hongzhao Lu (Food Research International, 2024)

Source appointment of δ13C in sediments of a maar lake in southern China: Implications of fossil fuel CO2 emissions - Meiling Guo; Yongming Han; Weiguo Liu; Yunning Cao; Dewen Lei; Weijian Zhou; Zhisheng An (Applied Geochemistry, 2024)

Minocycline attenuates the bilirubin-induced developmental neurotoxicity through the regulation of innate immunity and oxidative stress in zebrafish embryos - Guanghua Xiong; Tianle Hu; Yihong Yang; Haiyan Zhang; Meiling Han; Jiahao Wang; Yipeng Jing; Hongbo Liu; Xinjun Liao; Yong Liu (Toxicology and Applied Pharmacology, 2024)

Increased black carbon (soot) accumulation during the Anthropocene in a less-developed region of Xinjiang, northwestern China - Dewen Lei; Yongming Han; Changlin Zhan; Chong Wei; Yalan Tang; Meiling Guo; Jianing Zhang; Jingyu Li (Anthropocene, 2024)

Amino-functionalized nanocellulose aerogels for the superior adsorption of CO2 and separation of CO2/CH4 mixture gas - Wenkai Zhu; Meiling Chen; Jieun Jang; Minsu Han; Yeonggyun Moon; Junghwan Kim; Jungmok You; Song Li; Teahoon Park; Jeonghun Kim (Carbohydrate Polymers, 2024)

A new S-scheme heterojunction of 1D ZnGa2O4/ZnO nanofiber for efficient photocatalytic degradation of TC-HCl - Wenhui Chen; Tianxin Kang; Fenqi Du; Peipei Han; Meiling Gao; Peng Hu; Feng Teng; Haibo Fan (Environmental Research, 2023)

Characterisation of kapok fibre's biochar for arsenate adsorption removal from aqueous solution. - Kanfolo Franck Herve Yeo; Yingying Dong; Tongxuan Xue; Zhiwen Chen; Nan Zhang; Ye Yang; Liu Han; Meiling Liu; Ange Nsilani Kouediatouka; Hanse Pablick Patherny Lobo Mouguegue; Wendong Wang (Environmental Research, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Profiles and key drivers of bacteria/phage co-mediated antibiotic resistance genes during swine manure composting amended with humic acid - Meiling Shi; Zixuan Zhao; Xiaojuan Wang; Huakang Li; Jie Gu; Zilin Song; Ting Hu; Yifan Sun; Han Wang (Bioresource Technology, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

Mechanism of interactions between α-conotoxin RegIIA and carbohydrates at the human α3β4 nicotinic acetylcholine receptor - Meiling Zheng; Han-Shen Tae; Liang Xue; Tao Jiang; Rilei Yu (Marine Life Science & Technology, 2022)
Conotoxins are marine peptide toxins from marine cone snails. The α-conotoxin RegIIA can selectively act on human (h) α3β4 nicotinic acetylcholine receptor (nAChR), and is an important lead for drug development. The high-resolution cryo-electron microscopy structure of the α3β4 nAChR demonstrates several carbohydrates are located near the orthosteric binding sites, which may affect α-conotoxin binding. Oligosaccharide chains can modify the physical and chemical properties of proteins by changing the conformation, hydrophobicity, quality and size of the protein. The purpose of this study is to explore the effect of oligosaccharide chains on the binding modes and activities of RegIIA and its derivatives at hα3β4 nAChRs. Through computational simulations, we designed and synthesized RegIIA mutants at position 14 to explore the importance of residue H14 to the activity of the peptide. Molecular dynamics simulations suggest that the oligosaccharide chains affect the binding of RegIIA at the hα3β4 nAChR through direct interactions with H14 and by affecting the C-loop conformation of the binding sites. Electrophysiology studies on H14 analogues suggest that in addition to forming direct interactions with the carbohydrates, the residue might play an important role in maintaining the conformation of the peptide. Overall, this study further clarifies the structure–activity relationship of α-conotoxin RegIIA at the hα3β4 nAChR and, also provides important experimental and theoretical basis for the development of new peptide drugs.

Pigment profile and gene analysis revealed the reasons of petal color difference of crabapples - Ting Shen; Meiling Han; Qianrui Liu; Chen Yang; Jiaxin Meng; Houhua Li (Brazilian Journal of Botany, 2021)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Multiple timescale analysis of the urban heat island effect based on the Community Land Model: a case study of the city of Xi’an, China - Meiling Gao; Huanfeng Shen; Xujun Han; Huifang Li; Liangpei Zhang (Environmental Monitoring and Assessment, 2018)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Comparison of Multi-Slice Computed Tomographic Angiography and Dual-Source Computed Tomographic Angiography in Resectability Evaluation of Pancreatic Carcinoma - Yongmei Yu; Meiling Guo; Xiangyu Han (Cell Biochemistry and Biophysics, 2014)

Patterns of asynchrony for phytoplankton fluctuations from reservoir mainstream to a tributary bay in a giant dendritic reservoir (Three Gorges Reservoir, China) - Yaoyang Xu; Qinghua Cai; Meiling Shao; Xinqin Han (Aquatic Sciences, 2012)

Temporal Asynchrony of Trophic Status Between Mainstream and Tributary Bay Within a Giant Dendritic Reservoir: The Role of Local-Scale Regulators - Yaoyang Xu; Meiling Shao; Xinqin Han; Qinghua Cai (Water, Air, & Soil Pollution, 2011)

Factors regulating trophic status in a large subtropical reservoir, China - Yaoyang Xu; Qinghua Cai; Xinqin Han; Meiling Shao; Ruiqiu Liu (Environmental Monitoring and Assessment, 2010)